Lesson plan design for teaching mathematics in multicultural classrooms - Bianco, Giuseppe; Di Paola, Benedetto (Frontiers in Education, 2025)
This paper describes a mathematics professional development experience designed from an intercultural perspective. This resulted in a hybrid Lesson Study cycle conducted online over two half-school years (autumn 2023 and spring 2024). The first phase of this professional development program aimed to explore the challenges of teaching and learning mathematics in multicultural and multilingual contexts—an emerging issue for the Italian school system. In the subsequent phase of professional development, teachers, supported by researchers, approached the Lesson Study, creating teaching materials from an intercultural perspective, emphasizing cultural aspects. A key finding during the online Lesson Study phase was the need for a preliminary phase before developing a Lesson Plan. This necessity, which is shaped by the flexibility and challenges of online settings, aligns with the theoretical foundations of our professional development program. We named this preliminary stage the Lesson Plan Design phase. Here, the teachers discussed not only the content but also the structure of the Lesson Plan. Starting with an example provided by researchers, teachers worked on a design level and collaboratively co-constructed a shared Lesson Plan Template, integrating the key factors highlighted during the initial professional development phase. The shift from merely using or filling out a given Lesson Plan to designing a structure of Lesson Plan is explored through a specific case study. This case study, focused on the design phase, demonstrates how cultural themes addressed at the beginning of professional development influenced the structure and content of the Lesson Plan. The aim of this new phase is to establish an online community of teachers from the bottom. This step aligns with the standard Lesson Study approach, which assumes the existence of such a community from the outset. After this phase, of creating a cohesive community of teachers, the Lesson Study cycle, as described in the literature, can proceed.